PID Control Implementation and Tuning - Mansour, Tamer (IntechOpen, 2011)
The PID controller is considered the most widely used controller. It has numerous applications varying from industrial to home appliances. This book is an outcome of contributions and inspirations from many researchers in the field of PID control. The book consists of two parts; the first is related to the implementation of PID control in various applications whilst the second part concentrates on the tuning of PID control to get best performance. We hope that this book can be a valuable aid for new research in the field of PID control in addition to stimulating the research in the area of PID control toward better utilization in our life.